STATISTICAL ANALYSIS OF THE LEVEL OF MANUFACTURING TRAUMATIC IN THE FIELD OF INDUSTRY: Array - Buts, Yu.; Barbachin, V.; Krainiuk, O.; Osipova, Yu.; Pavlichenko, P. (Municipal economy of cities. Series: «Economy science», 2019)
The purpose of this work is a comparative analysis of the rating positions of sectoral injuries in Ukraine for general and fatal injuries. In connection with the evolution, scientific and technological progress, the possibility of improving production capacity, the replacement of manual labor, the number of machine-related accidents in production should be reduced to a minimum, and especially industrial mortality. However, the analysis of statistical data in a regional section showed that the state of occupational injuries in some administrative-territorial units remains extremely unsatisfactory. Therefore, it is interesting to conduct a similar study in the sectoral dimension. A comparative analysis of the rating positions of generalized assessments of structural changes in the level of occupational injuries by industries in Ukraine during the period was conducted. The article analyzes the state of occupational injuries in Ukraine by industries for the period from 2014 to 2017. According to the calculations, the level of occupational injuries in the sectoral aspect, as well as in the regional, is not devoid of uneven distribution of the number of accidents. Circular diagrams have been constructed, reflecting the distribution of sector shares by the number of injured persons in those years. The intensity of the changes that took place in 2017 compared with 2014 is much lower than in the regions, ie the level of sectoral injuries is a rather stable indicator, which, unfortunately, is not controlled and reduced by some sectors so far. According to the statistical calculations, the level of occupational injuries in the sectoral aspect, as well as in the regional [2], is not devoid of uneven distribution of the number of accidents that occurred in the production during the studied periods. Our further research will focus on the coverage and processing of longer-term statistics in order to model and predict occupational injuries in our state.